(untitled) (Applied Biological Research, 2011)
Leaves of apple cv. ‘Red Delicious’ and ‘Golden Delicious’ were randomly collected from commercial apple growing areas of four districts of Jammu and Kashmir State viz., Shopian, Pulwama, Bandipora and Kupwara for the detection of Apple mosaic virus (ApMV) by RT-PCR technique using coat protein gene-specific primers. ApMV was present in all the locations. RT-PCR amplified approximately 800 bp amplicons from 30 out of 276 leaf samples thereby confirmed the infection of ApMV in Kashmir. District Bandipora recorded highest disease incidence of 13.3% followed by Shopian (11.3%), Kupwara (10.2%) and Pulwama (8.6%). Nineteen of the 161 cv. ‘Red Delicious’ samples and 11 of the 115 ‘Golden Delicious’ samples were found RT-PCR positive.